Communication in Distributed Software Development: An exploratory study of Hybrid and Remote Teams - Severo, Ricardo Augusto Niederauer Flores; Lucena, Márcia Jacyntha Nunes Rodrigues; Medeiros Júnior, Josué Vitor de; de Andrade, Adrianne Paula Vieira (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2026: Anais do XXI Simpósio Brasileiro de Sistemas Colaborativos, 2026)
In Distributed Software Development (DSD) projects, communication is essential for collaboration among geographically dispersed members. Tools such as Slack support communication flows and activity coordination, helping teams overcome challenges imposed by distance. The growing adoption of distributed models has generated new team arrangements and reconfigured communication dynamics, highlighting the need for empirical studies on these contexts. This study aimed to understand communication dynamics in different DSD team arrangements, hybrid and remote. An exploratory multiple case study was conducted over 13 months, analyzing Slack data from two projects within the same institutional context in Brazil, complemented by participant observation and document analysis. The results show that both teams predominantly use private channels, suggesting this is a structural characteristic of communication via Slack, and that communication is shaped mainly by the structures established in collaboration tools, being more influenced by factors such as team size, role diversity, project domain, and management practices than by the team arrangement itself.